O hibridismo cultural em Lavoura arcaica e Dois irmãos: representações do imigrante libanês no Brasil - JARDIM, Cristiane Fernandes da Silva (2012)
This work aims to discuss the representation of the figure of Lebanese immigrant in Brazil in the novels Lavoura arcaica, of Raduan Nassar, and Dois irmãos, of Milton Hatoum. The comparative study has as its starting point the concept of diaspora, forced displacement of large masses or stimulated coming from one area to host various regions, to consider the issue of cultural hybridity in fictions. The research is aligned to historical facts about Lebanese immigration, the authors' biographical information and elements of Arab culture to compare the narratives, noting the similarities and dissimilarities in their respective thematic scenarios.